The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fped.2020.613641
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Changes in Plasma Short-Chain Fatty Acid Concentrations and Hypertension in Children With Chronic Kidney Disease

Abstract: Background: Some children with chronic kidney disease (CKD) develop hypertension faster than others. This may be attributable to endothelial dysfunction, among other reasons. Short-chain fatty acids (SCFAs), that is, acetate, butyrate, and propionate, are known for reducing cardiovascular risks via preserving endothelial function. This study aimed to investigate the association between changes in plasma SCFA concentrations and in cardiovascular and endothelial parameters in children with CKD.Methods: In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Several of these genera ( Feacalibacterium, Fusicatenibacter and Anaerostipes ), known to produce short-chain fatty acids, were present in lower abundance in the CKD_Ss+ group. Previously, it was shown that serum SCFAs were reduced in patients infected with S. stercoralis [ 21 ] and in CKD patients [ 38 ]. SCFAs are known for their effects not only on the healthy gut microbiome but also on renal function [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several of these genera ( Feacalibacterium, Fusicatenibacter and Anaerostipes ), known to produce short-chain fatty acids, were present in lower abundance in the CKD_Ss+ group. Previously, it was shown that serum SCFAs were reduced in patients infected with S. stercoralis [ 21 ] and in CKD patients [ 38 ]. SCFAs are known for their effects not only on the healthy gut microbiome but also on renal function [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, research on SCFAs in diabetic nephropathy and CKD is underway, but few studies have reported the efficacy of SCFAs in IgAN. A number of studies have found that serum SCFA levels in patients with CKD are significantly lower than those in healthy volunteers and that the administration of SCFAs could reduce the level of urinary toxins in patients and could delay the progression of the disease [17,[40][41][42][43]. SCFAs could also reduce the gene and/or protein expression of inflammatory cytokines, chemokines and profibrotic factors in the kidney tissue of diabetic mice and could protect diabetic mice from kidney disease [16].…”
Section: Discussionmentioning
confidence: 99%
“…An investigation that enrolled 105 children and adolescents with CKD found a difference in plasma acetate between children with and without hypertension, suggesting its preventive role for hypertension in children with CKD. In addition, reduced plasma butyrate was found in the advanced and stable blood pressure groups at the 1-year follow up, which may potentially be caused by the decline in eGFR [80]. In addition, Chai et al identified substantially lower production of SCFAs, including acetic acid, propionic acid, butyric acid, and iso-butyric acid, in IgAN patients compared with those in the control group [53].…”
Section: Gut Microbial Metabolites and Ckdmentioning
confidence: 98%